Exploring The Religio-Socio Ethical Dimensions of Ai-Driven Evangelism: Opportunities, Challenges, And Implications - Alao, Oluwafemi Joseph; Dairo, Afolorunso Olalekan (INTI International University, 2024)
This paper investigates the impact of AI-driven evangelism, focusing on its religiosocio ethical dimensions. It highlights the integration of artificial intelligence in religious practices, addressing its benefits such as broader access to spiritual content, personalized education, and improved engagement with younger audiences alongside significant challenges, including concerns over authenticity, empathy, and ethical implications of machine-mediated guidance. The study stresses the importance of establishing ethical frameworks for AI use within religious institutions. Recommendations include developing ethical guidelines that align with theological principles, providing ongoing education for religious leaders on AI, and engaging congregations in discussions about technology integration. The paper concludes by advocating for balanced approaches to AI that enhance spiritual experiences while respecting diverse faith practices. Overall, it emphasizes the necessity for continued dialogue among religious communities to successfully navigate the complexities introduced by AI in spiritual life.